Analysis of phase change dynamics by using fin in a 3D tall cavity and modeling with artificial neural network - Ortop, Hakan F.; Selimefendigil, Fatih; Cosanay, Hakan (Elsevier Sci Ltd, 2022)
Computational fluid dynamics studies on phase change process dynamics, heat transfer and fluid flow in a 3D tall cavity are performed by using finite volume method. Both finned and un-finned cases are considered. Thermal transport enhances with higher values of Grashof number while phase change process is further improved by installing a fin within the cavity. The fin and its parameters can be used for thermal management and control of phase change dynamics As compared to no-fin case, 40% and 8% higher melt fraction amounts are obtained by using fin at t = 400 s and t = 1200s. The fin size and its location in the 3D tall cavity is found as an excellent tool for phase transition control. The best phase change process performance is achieved when the fin is used in the middle part of the 3D tall prism as l/W = 0.5, h/W = 0.05 and w/W = 0.4. Dynamics of phase change is estimated by using feed-forward neural networks for finned and un-finned configurations.
Keywords: Phase change dynamics; Finite element method; 3D tall cavity; Neural networks